Tindak Pidana dan Jerat Hukum Penadahan Bagi Pedagang Barang Bekas - Aqila Nanda Zulta; Diana Putri Lorensia; Sertika Banjarnahor; M. Hendri; Zulvan Lindan Arrasyid (Disiplin : Majalah Civitas Akademika Sekolah Tinggi Ilmu Hukum sumpah Pemuda, 2025)
This article examines the boundaries that distinguish second-hand goods traders as participants in the criminal act of fencing, as well as the legal protections available to them. The study employs a normative legal research method with a descriptive approach, drawing on primary and secondary legal materials. The findings indicate that not all second-hand goods traders can be classified as fences, but only when both objective and subjective elements under Article 480 of the Indonesian Criminal Code are fulfilled. To obtain legal protection, traders must adopt preventive measures, particularly by exercising caution in transactions, thereby avoiding potential criminal liability.